Culturally Relevant Management Education: Insights from Experience in Nunavut (Alberta Journal of Educational Research, 2005)
The author’s experience with a Nunavut business management education program illustrates how to develop culturally relevant organizational behavior curriculum. The process initially involved interviews with Inuit Elders about culturally appropriate responses to scenarios of cultural conflicts in the workplace identified by Inuit managers. The author then engaged in an experiential learning project working with an Aboriginal organization in southern Canada to develop a culturally appropriate organizational culture. The experience highlighted the importance of cross-cultural management educators recognizing diversity in another culture while actively demonstrating respect for and interest in the other culture’s values and beliefs. The author recommends that in an increasingly globalized world, cross-cultural management educators undertake similar efforts to develop organizational behavior curriculum that reflects culturally diverse world views.